Clinical Significance of Histogram Parameters on Elastography in Patients With Papillary Thyroid Microcarcinomas. Issue 3 (September 2017) - Yoon, Hee Yeun; Lee, Ji Hye; Kim, Young Eun; Kim, Eun-Kyung; Moon, Hee Jung; Yoon, Jung Hyun; Park, Vivian Y.; Kwak, Jin Young
Abstract : Objective: The purpose of our study was to determine objective histogram parameters on elastography that could predict poor prognosis factors of conventional papillary thyroid microcarcinomas (PTMCs). Methods: From September to November in 2012, 79 patients with a diagnosis of PTMCs were included. Mean values of clinicopathologic variables and histogram parameters on elastography were compared between groups with or without poor prognostic factors using the Student t test, χ 2 test, or Fisher exact test. Multivariate logistic regression analysis adjusted for age, gender, and size was performed to investigate independent elastography parameters predicting extrathyroidal extension, lymph node metastasis, and high TNM stage (III–IV). Results: Of 79 patients with PTMCs, 32 (40.5%) had extrathyroidal extension, 14 (17.7%) had lymph node metastasis, and 18 (22.8%) received a diagnosis with a high TNM stage. None of the histogram parameters on elastography had significant associations with any of the poor prognostic factors. Conclusions: There were no significant associations between all histogram parameters on elastography and known poor prognostic factors such as extrathyroidal extension, lymph node metastasis, and high TNM stage in patients with PTMCs.